Revision of the Oriental genus Zavatilla Tsuneki (Hymenoptera, Mutillidae, Trogaspidiini), with descriptions of two new species - Zhou, Hu-Ting; Lelej, Arkady S.; Williams, Kevin A.; Liu, Jing-Xian (Zootaxa, 2018)
Four species of the genus Zavatilla Tsuneki, 1993 are reviewed. An updated diagnosis of the genus is given and two new sex associations are proposed. Two new species, Z. xuzaifui Zhou, Lelej et Williams, sp. nov. (China: Guangdong, Yunnan, Hainan; Vietnam) and Z. nepalensis Zhou et Lelej, sp. nov. (Nepal) are described. Mutilla logei Zavattari, 1913 is proposed as junior synonym of Z. gutrunae (Zavattari, 1913). The status of Z. gutrunae flavotegulata (Chen, 1957) is updated to specific level. A key to the known species of Zavatilla is given for males and females.